Tafsir Maqashidi as an Alternative Approach in Interpreting the Qur'an - Tri Wahyu Hidayati (Institut Agama Islam Negeri (IAIN) Salatiga, 2020)
Due to al-Qur'an shalih likulli zaman wa makan, al-Qur'an should be interpreted appropriately to the demands of life. Apparently, life has changed in various circumstances, in lifestyles, human relations, globalization, migration, advanced science, and sophisticated technology. The modernization has led to serious problems related to the Qur’an as the main source of Islamic jurisprudence emerging “unable to operate”, except by a few Muslims. If there is no re-interpretation of the Qur’anic verses, there is a possibility Islamic jurisprudence will be rejected, considered irrelevant, and counter-productive to the needs of the life. To be able to reinterpret, a maqashidi interpretation approach is required to construe the Qur’an, especially in the ethics-legal verses. There are two significant implications in the maqashidi’s interpretation approach; first, the maqashidi interpretation paradigm is the mindset and perspective of the Qur’an and its interpretation with the concept of maqashid al-shari'ah as its starting point. The concept of maqashid becomes the main basis in reasoning and which forms the interpretation system. Second, the method of interpreting maqashidi’s approach emphasizes on three pillars, namely historical awareness (al-wa’yu al-tarikh), theoretical awareness (al-wa'yu al-nazhari), praxis awareness (al-wa'yu al-‘amali). Practically, the steps of maqashidi's interpretation are contextualization, decontextualization, and re-contextualization.